A Geopolitical Study on the New Provincial Hospital during the Period of Governor-General Saito - Bangweon LEE (Uisahak, 2022)
This study examines the characteristics of fifteen Jahye hospitals and provincial hospitals which were established or relocated during Governor-General Saito’s regime. The purpose of this study is to analyze these hospitals by connecting them to the directions of Japanese colonial policies, the political beliefs of the governor-general, and their necessity by the local people. The period of expansion of provincial hospitals was divided in to three different periods. The periods are divided as follows: the first appointment of Saito as the governor-general, the period when Jahye hospitals turned into provincial hospitals, and when Saito got reappointed as the governor-general. It analyzes the natural and human geographical environment of each region where Jahye and the provincial hospitals were organized. Based on this analysis, it investigates the geopolitical features of Jahye and provincial hospitals which were established on the Governor-General Saito era.First, the areas that the Joseon Governor-General was interested in establishing Jahye and the provincial hospitals were military points useful for keeping Russia in check and managing the Manchurian region. In addition, those areas were rich in resources needed by Japan and transportation centers which were useful for the collection and distribution of goods. Second, the regions where provincial hospitals were built were rice-producing areas and leading export ports which were related to the rice production growth plan in the early 1920s. Also, the region’s own economic power was able to run the hospitals. Third, at the stage of deciding to install a new provincial hospital, there were conflicts due to concerns over the deterioration of the status of nearby areas and existing regions and the difficulty of operating provincial hospitals. Fourth, each provincial hospital was divided into independent provincial hospitals, provincial branch members, provincial branch offices, etc. according to the region’s size and population. Among them, some provincial branch members and provincial branch offices were promoted to independent hospitals due to the development and expansion of the region and the increase in the number of patients who used the hospitals. Also, it was revealed that in the process of expanding a city, some regional hospitals were turned into provincial hospitals.In conclusion, the provincial hospitals which were newly built in during the Governor-General Saito era were established in military and economically useful areas for the Japanese colonial rule. Also, transportation facilities such as railroads were installed in the areas, and this lead to concentration of infrastructure and industrial facilities such as companies and factories, which in turn made possible the increase of population, especially the population of Japanese people.